Bio-efficacy of post emergence herbicides in boro rice nursery as well as main field and their residual effects on non-target microorganisms - Kundu, Rajib; Mondal, Mousumi; Garai, Sourav; Mondal, Ramyajit; Poddar, Ratneswar (ORYZA-An International Journal of Rice, 2020)
Field experiments were conducted at research farm of Bidhan Chandra Krishi Viswavidyalaya, Kalyani, West Bengal, India (22°97' N latitude and 88°44' E longitude, 9.75 m above mean sea level) under natural weed infestations in boro season rice (nursery bed as well as main field) during 2017-18 and 2018-19 to evaluate the herbicidal effects on weed floras, yield, non-target soil organisms to optimize the herbicide use for sustainable rice-production. Seven weed control treatments including three doses of bispyribac-sodium 10% SC (150,200, and 250 ml ha-1), two doses of fenoxaprop-p-ethyl 9.3% EC (500 and 625 ml ha-1), one weed free and weedy check were laid out in a randomized complete block design, replicated thrice. Among the tested herbicides, bispyribac-sodium with its highest dose (250 ml ha-1) resulted in maximum weed control efficiency, treatment efficiency index and crop resistance index irrespective of weed species and dates of observation in both nursery as well as main field. Similar treatment also revealed maximum grain yield (5.20 t ha-1), which was 38.38% higher than control, closely followed by Fenoxaprop-p-ethyl (625 ml ha-1) had high efficacy against grasses,sedge and broadleaf weed flora. Maximum net return (Rs. 48765 ha-1) and benefit cost ratio (1.72) were obtained from the treatment which received bispyribac-sodium @ 250 ml ha-1. Based on overall performance, the bispyribac-sodium (250 ml ha-1) may be considered as the best herbicide treatment for weed management in transplanted rice as well as nursery bed.